THE ROLE OF UKRAINIAN RAILWAY TRANSPORT IN MODERN LOGISTIC PROCESSES - Lomotko, D. V.; Prymachenko, H. O.; Hryhorova, Y. I. (Science and Transport Progress, 2019)
Purpose. As Ukraine actively develops its transport and logistics network taking into account the modern changes, the ever-increasing trade volume between the Europe and Asia, presents a good opportunity for increasing interoperability for the networks of international railway transportations. The study is aimed to consider in detail main components of railway interoperability and possible ways for achievement of their interaction. Methodology. The idea of interoperability was taken as a basis as a part of logistic system at railway. The crossing of different types of gauges was analyzed on the example of collaboration of Ukraine with European and Asian countries due to the increased freight traffic volume between them. Findings. Taking into account the basic technical parameters unifying the railway operation we found out the following principles: to agree upon a set of technical parameters, essential for the interoperability of the entire region; to determine the values and methods for agreement of the technical parameters to achieve technical interoperability; to decide on gradual implementation of technical interoperability, starting from the international corridors in a coordinated way depending on the priorities of international transportations. Originality. We considered the value of interoperability as a part of railway logistic systems. Practical value. The obtained results of search can be used during implementation of common platform of Ukraine`s collaboration with other countries related to the railway interoperability by establishing common base for work in prospective collaboration.